Seismogram Analysis of Earthquakes in Sumatra-Java at HYB Observatory Station - Bagus Jaya Santosa (Indonesian Journal of Physics, 2010)
The S wave velocity across the earth structure under Indian Ocean has been investigated through seismogram analysis in the time domain and three Cartesians components simultaneously from earthquakes occurred in Sumatra in which the data is recorded in HYB observatory station, India. The main data set are comparison between the measured and the synthetic seismograms, instead the travel time data or dispersion analysis, as commonly used by other seismologists. The synthetic seismogram is calculated with the GEMINI method using the CMT solution and the vertical isotropy of PREM earth model that is generally referred by other seismologists. The above seismogram comparison shows that the global earth mantle of PREM gives deviating synthetic seismogram and has later arrival times than those from measurement. The gradient βh in the upper mantle layers was altered to positive from its negative slope as stated in the PREM model, and positive corrections are added to the zero order of polynomials coefficients of S velocity structure in all earth mantle layers. The excellent fitting, as well as travel time and waveform, were achieved on the S wave, Love and Rayleigh surface waves, as well as the ScS and ScS core reflected waves.